A high temperature self-limiting temperature heating belt
By using polyvinyl sheathing material in the sheath layer of the high-temperature self-limiting temperature tracing and adding modified carbon black and aging resistance agent, the problem of poor thermal oxygen aging resistance of existing materials is solved, and stronger thermal oxygen aging resistance and longer service life are achieved.
Patent Information
- Application Number
- CN202211166231.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-09-23
AI Technical Summary
The existing high-temperature self-limiting temperature tray insulation sheath material has poor thermal oxygen aging performance, and the anti-aging agent is unstable and easy to migrate and precipitate at high temperatures, resulting in deterioration of insulation performance after the use time increases.
Polyvinyl sheath is used as the sheath layer, and by adding modified carbon black and aging-resistant agent to the thermoplastic polyethylene, a sheath with antioxidant and hindered amine structure is prepared to improve the anti-thermal oxygen aging performance of the material.
It effectively improves the anti-thermal oxygen aging performance of the self-limited temperature tracing, slows down the breaking speed of the polyethylene molecular chain under hot oxygen conditions, and extends the service life of the insulating sheath material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of self-limiting temperature heating belt preparation, and in particular, relates to a high-temperature self-limiting temperature heating belt. Background Art
[0002] High temperature heating belt is a functional polymer material, which has the dual functions of converting electrical energy into thermal energy and automatically adjusting and limiting temperature. Its self-limiting temperature characteristic is achieved by a composite material formed by conductive particles (such as carbon black, graphite, metal powder, etc.) and fluorine-containing resin (such as PVDF, F40, PFA, etc.) - functional polymer material. It can be used in pipes, valve bodies, pump bodies, storage tanks and other devices, and its heating temperature is higher than that of common steam heating and ordinary self-limiting temperature heating belt, which can reach 130-150℃, so it can meet higher temperature requirements. However, due to the high heating temperature, it often causes thermal aging to its sheath material. The existing high temperature self-limiting temperature heating belt's insulating sheath material is mostly made of polypropylene or ethylene propylene rubber, which has poor resistance to heat and oxygen aging. Although some antioxidants are added, these antioxidants are unstable at high temperatures and are easy to migrate and precipitate. As the heating belt is used for a longer time, the performance of the insulating sheath material becomes worse. Summary of the invention
[0003] In order to solve the technical problems mentioned in the background technology, the present invention provides a high-temperature self-limiting temperature heating belt.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A high-temperature self-limiting temperature heating belt, comprising two copper core busbars arranged in parallel, a heating core layer covering and connecting the two copper core busbars, the heating core layer is wrapped with an insulating layer, the insulating layer is wrapped with a shielding layer, and a sheath layer is arranged outside the shielding layer;
[0006] Among them, the copper core busbar is tinned copper stranded wire or nickel-plated copper stranded wire, the heating core layer is made of heating granular material extruded and coated on the surface of the copper core busbar at 210-230℃, the insulation layer is made of low-smoke halogen-free flame-retardant thermoplastic polyolefin, the shielding layer is woven from a mixed metal fiber, and the sheath layer is made of polyethylene-based sheath material.
[0007] Further, the heat generating pellets are prepared by the following steps:
[0008] By weight, 65-90 parts of polyvinylidene fluoride, 5-10 parts of paraffin, 0.5-1 part of antioxidant, 4-15 parts of graphite conductive particles, and 0.5-1 part of N,N′-diacetyladipic acid dihydrazide are mixed evenly in a high-speed mixer, and then transferred to a twin-screw extruder for extrusion and granulation at 210-230°C to obtain exothermic pellets.
[0009] Further, the polyethylene-based sheath material is made by the following steps:
[0010] By weight, 100 parts of thermoplastic polyethylene, 2-3 parts of vinyl chloride acrylic acid, 0.5-3 parts of diisopropylbenzene peroxide, 2.5-3 parts of modified carbon black and 1-2 parts of anti-aging agent are added into a mixer, stirred for 5-10 minutes and then transferred into a twin-screw extruder, extruded and granulated at a temperature of 100-140°C to obtain a polyethylene-based sheath material.
[0011] Further, the anti-aging agent is prepared by the following steps:
[0012] Step A1, under nitrogen protection, add p-tert-butylphenol into a four-necked flask, then add dichloroacetic acid and cyclohexane, heat to reflux for 6-8h, after the reaction is completed, cool to room temperature, filter, wash the filter cake, and dry to obtain substance a, the amount ratio of p-tert-butylphenol, dichloroacetic acid and cyclohexane is 0.2mol:0.1mol:100-150mL;
[0013] Step A2, 1,2,7,8-diepoxyoctane and N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine are added to a three-necked flask, salicylic acid is added as a catalyst, and the mixture is reacted with magnetic stirring at 150° C. for 12-14 hours under nitrogen protection. After the reaction is completed, the mixture is cooled in a dark place, and dichloromethane is added to dissolve the mixture. The mixture is washed with a 3wt% sodium bicarbonate solution, dried, and dichloromethane is removed by rotary evaporation to obtain substance b, wherein the molar ratio of 1,2,7,8-diepoxyoctane to N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine is 1:2.2, and the amount of salicylic acid used is 2-3% of the total mass of 1,2,7,8-diepoxyoctane and N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine;
[0014] Step A3, add substance a, substance b, p-toluenesulfonic acid and toluene to a three-necked flask, stir for 3-5 minutes, heat to reflux for 8-10 hours, cool to room temperature after the reaction, wash with 0.1 mol / L sodium bicarbonate solution, and rotary evaporate the organic phase to obtain an anti-aging agent. The amount ratio of substance a, substance b, p-toluenesulfonic acid and toluene is 3.93g:5.52g:0.2-0.3g:90-120mL.
[0015] Furthermore, the thermoplastic polyethylene is one or more of low-density polyethylene, high-density polyethylene and linear low-density polyethylene mixed in any proportion.
[0016] Furthermore, the modified carbon black is obtained by treating carbon black with a silane coupling agent KH-560.
[0017] Beneficial effects of the present invention:
[0018] The present invention provides a high-temperature self-limiting temperature heating belt, which is prepared from a fluorine-containing resin and conductive ions and other materials to produce a heating granular material, and the heating temperature is 130-150°C. In order to overcome the problem of poor heat aging resistance of the high-temperature heating belt, the present invention adopts a polyethylene-based sheath material to prepare a sheath layer, and the polyethylene sheath material is made of thermoplastic polyethylene as a base material, and is added with carbon black and an anti-aging agent and other materials, wherein the anti-aging agent contains an antioxidant phenolic hydroxyl group and an anti-aging hindered amine structure and contains an active hydroxyl group, which can not only undergo a chemical grafting reaction with the modified carbon black, but also overcome the existing antioxidant The problem of easy migration and precipitation can be solved, and the active free radicals R· and ROO· generated by the matrix molecular chain during the thermal oxidative aging process can be effectively captured, which can effectively inhibit the autocatalytic reaction of the polyethylene molecular chain, and is beneficial to slowing down the breakage rate of the polyethylene molecular chain under thermal oxidative conditions, thereby improving the thermal oxidative aging resistance of the composite material. The modified carbon black has a strong light absorption property, which can protect the surface of the material from damage by ultraviolet rays, thereby greatly reducing the photo-oxidative degradation of the polyethylene sheath material. Therefore, the self-limiting temperature heating belt prepared by the present invention not only has a high heating temperature, but also has a strong aging resistance. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] Example 1
[0021] Modified carbon black is made by the following steps:
[0022] Anhydrous ethanol and deionized water were mixed in a volume ratio of 2:3, acetic acid was added to adjust the pH to 4, silane coupling agent KH-560 was added, and the mixture was stirred and hydrolyzed at room temperature for 2 hours. Carbon black was added and ultrasonically dispersed for 30 minutes. The mixture was heated to 80°C and stirred for reaction for 4 hours. After the reaction was completed, the mixture was filtered and the filter cake was dried to obtain modified carbon black. The amount of silane coupling agent KH-560 was 3% of the mass of carbon black.
[0023] Example 2
[0024] The anti-aging agent is prepared by the following steps:
[0025] Step A1, under nitrogen protection, add 0.2 mol of p-tert-butylphenol into a four-necked flask, then add 0.1 mol of dichloroacetic acid and 100 mL of cyclohexane, heat to reflux and react for 6 hours. After the reaction is completed, cool to room temperature, filter, wash the filter cake with n-hexane, and dry to obtain substance a;
[0026] Step A2, 0.1 mol of 1,2,7,8-diepoxyoctane and 0.22 mol of N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine were added to a three-necked flask, salicylic acid was added as a catalyst, and the mixture was reacted with magnetic stirring at 150° C. for 12 h under nitrogen protection. After the reaction, the mixture was cooled in a dark place, and dichloromethane was added to dissolve the mixture. The mixture was washed with 3 wt% sodium bicarbonate solution, dried, and dichloromethane was removed by rotary evaporation to obtain substance b. The amount of salicylic acid used was 2% of the total mass of 1,2,7,8-diepoxyoctane and N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine.
[0027] Step A3, add 3.93g substance a, 5.52g substance b, 0.2g p-toluenesulfonic acid and 90mL toluene into a three-necked flask, stir for 3min, heat to reflux for 8h, after the reaction is completed, cool to room temperature, wash with 0.1mol / L sodium bicarbonate solution, and rotary evaporate the organic phase to obtain an anti-aging agent.
[0028] Example 3
[0029] The anti-aging agent is prepared by the following steps:
[0030] Step A1, under nitrogen protection, add 0.2 mol of p-tert-butylphenol into a four-necked flask, then add 0.1 mol of dichloroacetic acid and 150 mL of cyclohexane, heat to reflux for 8 hours, after the reaction is completed, cool to room temperature, filter, wash the filter cake with n-hexane, and dry to obtain substance a;
[0031] Step A2, 0.1 mol 1,2,7,8-diepoxyoctane and 0.22 mol N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine were added to a three-necked flask, salicylic acid was added as a catalyst, and the mixture was reacted with magnetic stirring at 150° C. for 14 h under nitrogen protection. After the reaction, the mixture was cooled in a dark place, and dichloromethane was added to dissolve the mixture. The mixture was washed with 3 wt% sodium bicarbonate solution, dried, and dichloromethane was removed by rotary evaporation to obtain substance b. The amount of salicylic acid used was 3% of the total mass of 1,2,7,8-diepoxyoctane and N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine.
[0032] Step A3, add 3.93g substance a, 5.52g substance b, 0.3g p-toluenesulfonic acid and 120mL toluene into a three-necked flask, stir for 5min, heat to reflux for 10h, after the reaction is completed, cool to room temperature, wash with 0.1mol / L sodium bicarbonate solution, and rotary evaporate the organic phase to obtain an anti-aging agent.
[0033] Example 4
[0034] A high-temperature self-limiting temperature heating belt, comprising two copper core busbars arranged in parallel, a heating core layer covering and connecting the two copper core busbars, the heating core layer is wrapped with an insulating layer, the insulating layer is wrapped with a shielding layer, and a sheath layer is arranged outside the shielding layer;
[0035] Among them, the copper core busbar is tinned copper stranded wire or nickel-plated copper stranded wire, the heating core layer is made of heating granular material extruded and coated on the surface of the copper core busbar at 210-230℃, the insulation layer is made of low-smoke halogen-free flame-retardant thermoplastic polyolefin, the shielding layer is woven from a mixed metal fiber, and the sheath layer is made of polyethylene-based sheath material.
[0036] The heat-generating pellets are made by the following steps:
[0037] By weight, 65 parts of polyvinylidene fluoride, 5 parts of paraffin, 0.5 parts of antioxidant, 4 parts of graphite conductive particles, and 0.5 parts of N,N′-diacetyladipic acid dihydrazide are mixed evenly in a high-speed mixer, and then transferred to a twin-screw extruder for extrusion granulation at 210-230°C to obtain exothermic pellets.
[0038] The polyethylene-based sheath material is made by the following steps:
[0039] By weight, 100 parts of high-density polyethylene, 2 parts of vinyl chloride acrylic acid, 0.5 parts of diisopropylbenzene peroxide, 2.5 parts of modified carbon black of Example 1, and 1 part of anti-aging agent of Example 2 were added into a mixer, stirred for 5 minutes, and then transferred to a twin-screw extruder, extruded and granulated at a temperature of 100-140°C to obtain a polyethylene-based sheath material.
[0040] Example 5
[0041] A high-temperature self-limiting temperature heating belt, comprising two copper core busbars arranged in parallel, a heating core layer covering and connecting the two copper core busbars, the heating core layer is wrapped with an insulating layer, the insulating layer is wrapped with a shielding layer, and a sheath layer is arranged outside the shielding layer;
[0042] Among them, the copper core busbar is tinned copper stranded wire or nickel-plated copper stranded wire, the heating core layer is made of heating granular material extruded and coated on the surface of the copper core busbar at 210-230℃, the insulation layer is made of low-smoke halogen-free flame-retardant thermoplastic polyolefin, the shielding layer is woven from a mixed metal fiber, and the sheath layer is made of polyethylene-based sheath material.
[0043] The heat-generating pellets are made by the following steps:
[0044] By weight, 70 parts of polyvinylidene fluoride, 8 parts of paraffin, 0.8 parts of antioxidant, 10 parts of graphite conductive particles, and 0.8 parts of N,N′-diacetyladipic acid dihydrazide are taken, and the above raw materials are mixed evenly in a high-speed mixer, and then transferred to a twin-screw extruder for extrusion and granulation at 210-230°C to obtain exothermic pellets.
[0045] The polyethylene-based sheath material is made by the following steps:
[0046] By weight, 100 parts of high-density polyethylene, 2.5 parts of vinyl chloride acrylic acid, 2 parts of diisopropylbenzene peroxide, 2.8 parts of modified carbon black of Example 1, and 1.5 parts of anti-aging agent of Example 2 were added into a mixer, stirred for 8 minutes, and then transferred to a twin-screw extruder, extruded and granulated at a temperature of 100-140°C to obtain a polyethylene-based sheath material.
[0047] Example 6
[0048] A high-temperature self-limiting temperature heating belt, comprising two copper core busbars arranged in parallel, a heating core layer covering and connecting the two copper core busbars, the heating core layer is wrapped with an insulating layer, the insulating layer is wrapped with a shielding layer, and a sheath layer is arranged outside the shielding layer;
[0049] Among them, the copper core busbar is tinned copper stranded wire or nickel-plated copper stranded wire, the heating core layer is made of heating granular material extruded and coated on the surface of the copper core busbar at 210-230℃, the insulation layer is made of low-smoke halogen-free flame-retardant thermoplastic polyolefin, the shielding layer is woven from a mixed metal fiber, and the sheath layer is made of polyethylene-based sheath material.
[0050] The heat-generating pellets are made by the following steps:
[0051] By weight, 90 parts of polyvinylidene fluoride, 10 parts of paraffin, 1 part of antioxidant, 15 parts of graphite conductive particles, and 1 part of N,N′-diacetyladipic acid dihydrazide are mixed evenly in a high-speed mixer, and then transferred to a twin-screw extruder for extrusion granulation at 210-230°C to obtain exothermic pellets.
[0052] The polyethylene-based sheath material is made by the following steps:
[0053] By weight, 100 parts of high-density polyethylene, 3 parts of vinyl chloride acrylic acid, 3 parts of diisopropylbenzene peroxide, 3 parts of modified carbon black of Example 1, and 2 parts of anti-aging agent of Example 3 were added into a mixer, stirred for 10 minutes, and then transferred to a twin-screw extruder, extruded and granulated at a temperature of 100-140°C to obtain a polyethylene-based sheath material.
[0054] Comparative Example 1
[0055] The anti-aging agent in Example 4 was substituted for N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, and the remaining raw materials and preparation process were the same as in Example 4.
[0056] Comparative Example 2
[0057] The modified carbon black in Example 5 is used to replace the carbon black, and the remaining raw materials and preparation process are the same as Example 5.
[0058] The sheath materials of the self-limiting temperature heating belts prepared in Examples 4-6 and Comparative Examples 1-2 were tested, and the tensile strength was tested with reference to GB / T2951 "General Test Methods for Insulation and Sheath Materials of Electric Cables and Optical Cables", and the artificial weathering test performance was tested in accordance with the national standard GB12527-2008 "Overhead Insulated Cables with Rated Voltages of 1 kV and Below", and the tensile strength change rate of the insulation layer of the heating belt was tested. The test results are shown in Table 1:
[0059] Table 1
[0060]
[0061] It can be seen from Table 1 that compared with Comparative Examples 1-2, the self-limiting temperature heating belts prepared in Examples 4-6 have better performance.
[0062] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0063] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A high temperature self-limiting temperature heating belt, characterized in that: It comprises two copper core busbars arranged in parallel, a heating core layer covering and connecting the two copper core busbars, an insulating layer wrapped outside the heating core layer, a shielding layer wrapped outside the insulating layer, and a sheath layer arranged outside the shielding layer; The sheath layer is made of a polyethylene-based sheath material, and the polyethylene-based sheath material is made by the following steps: By weight, 100 parts of thermoplastic polyethylene, 2-3 parts of vinyl chloride acrylic acid, 0.5-3 parts of dicumyl peroxide, 2.5-3 parts of modified carbon black, and 1-2 parts of anti-aging agent are added into a mixer, stirred and transferred into a twin-screw extruder, and extruded and granulated at a temperature of 100-140°C; The anti-aging agent is prepared by the following steps: Step A1, under nitrogen protection, p-tert-butylphenol, dichloroacetic acid and cyclohexane are mixed, and the temperature is raised to reflux for reaction for 6-8 hours to obtain substance a; Step A2, 1,2,7,8-diepoxyoctane and N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine were mixed, salicylic acid was added, and the mixture was stirred at 150° C. for 12-14 h under nitrogen protection to obtain substance b; Step A3, add substance a, substance b, p-toluenesulfonic acid and toluene into a three-necked flask, stir and reflux for 8-10 hours; The dosage ratio of p-tert-butylphenol, dichloroacetic acid and cyclohexane is 0.2 mol: 0.1 mol: 100-150 mL; The molar ratio of 1,2,7,8-diepoxyoctane to N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine is 1:2.2, and the amount of salicylic acid is 2-3% of the total mass of 1,2,7,8-diepoxyoctane and N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine; The usage ratio of substance a, substance b, p-toluenesulfonic acid and toluene is 3.93 g:5.52 g:0.2-0.3 g:90-120 mL.
2. A high temperature self-limiting temperature heating belt according to claim 1, characterized in that: The modified carbon black is obtained by treating carbon black with silane coupling agent KH-560.
Citation Information
Patent Citations
Self-regulating electric tracing band specially for fire fighting
CN106332334A
Anti-aging sealant
CN109280230A